Normative Juridical Analysis Of Weakness Of Control Of Judges Integrity - Rahmatsyah, Rahmatsyah (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Judge is a profession that requires high integrity. However, Code of Ethics and Judges’ Code of Conduct violations were carried out by unscrupulous judicial institutions in Indonesia. Thus, the aim of this study are to analyze and describe the weaknesses of the supervisory system which have an impact on the weak integrity of judges resulting in violations of Code of Ethics and Code of Conduct for Judges. This research was conducted with a normative juridical approach. The results of this study are as follows. 1) The guarantee of judge integrity is carried out by monitoring the behavior of judges, namely internal supervision by the Supreme Court and external supervision by the Judicial Commission. External supervision to minimize the occurrence of subjectivity in the results of internal supervision. 2) External supervision does not rule out the possibility of violations of the code of ethics and behavior, this is due to errors in interpreting the Judicial Commission's position, ambiguity and incomplete supervision procedures in the Judicial Commission Law regulations. 3) Public supervision of judges needs to be carried out to monitor the behavior of judges who cannot be supervised intensely by the supervisory body. 4) The integrity of judges is correlated with the International Framework for Court Excellence program which has core values that must be realized by judicial institutions so that they can realize legal justice for all people. Conclusion: the weak integrity of judges is due to unclear and uncomplete rules, inaccurate implementation and lack of innovation in supervision.